Risk Management Analysis of PT Fairus Permata Mulia Pekalongan - Nila Salma; Kurnia Muhajarah (Yayasan Riset dan Pengembangan Intelektual, 2023)
The umrah travel industry has experienced significant growth, but with this growth comes various risks that need to be carefully managed. PT. Fairus Permata Mulia, as a provider of umrah tickets, faces risks such as regulatory changes, ticket price fluctuations, health risks, and the safety of pilgrims. Risk management is a key factor in ensuring the smooth operation and satisfaction of the pilgrims. This research aims to identify the risk management strategies applied by PT. Fairus Permata Mulia. The research method used is qualitative, with in-depth interviews as the primary data source. The results show that the company has implemented various strategies, such as phased ticket reservations, ticket sales four months before departure, careful data input, and the selection of suitable umrah packages. The company has also anticipated risks through cancellation provisions. This research provides a deep understanding of the complexity of risk management in the umrah travel industry, specifically for PT. Fairus Permata Mulia, emphasizing the importance of risk management in maintaining business sustainability and customer satisfaction.